An evaluation of the policies instituted by the government of Zimbabwe in promoting survival and growth of SMEs: the case of Glenview area 8 SMEs - Nyamwanza, L.; Paketh, L.; Mhaka, C.; Makaza, F.; Moyo, Nokuthula G. (Novelty Journals, 2016)
The main objective of this study is to evaluate the policies instituted by the government of Zimbabwe in promoting the survival and growth of SMEs using a case of SMEs in Glen View Area 8. This was done with a view to draw up strategies aimed at improving the contribution of SMEs to Zimbabwe’s GDP. The research used a qualitative research design, a random sample was chosen to which a survey questionnaire was administered to collect data. Interviews were also conducted with personnel from the Ministry of Small and Medium Enterprises and Harare City Council Department of Health and Social Services. Findings indicated that little had been done by government in addressing SME concerns and accord priority to the SMEs so that they are enabled to contribute to the betterment of the economy. Challenges found to be facing SMEs were issues such as capital availability, difficulties in procuring raw materials, low technological capabilities, and difficulties in securing permits and licences. The study recommended that SMEs are a significant sector that should otherwise be contributing significantly to the economy and recommended that government should prioritise SMEs by establishing finance schemes, training programmes and encourage clustering.